Acquired Brain Injury, Parenting, Social Work, and Rehabilitation: Supporting Parents to Support Their Children. Issue 3 (12th December 2016) - Holloway, Mark; Tyrrell, Lauren
ABSTRACT: Growing numbers of adults live with the consequences of acquired brain injury (ABI). Those affected frequently require medical input, rehabilitation, and social care. Individuals could suffer from a range of impairments that affect functional abilities. Limited attention has been paid to parenting with an ABI both within the social work and ABI literature. Parents with ABI present specific challenges to social workers and rehabilitationists. Case studies are used to illustrate how services can work to protect and support all parties, facilitating engagement with rehabilitation. The article concludes by considering the knowledge needed to facilitate engagement with rehabilitation and support.